Identifikasi homolog TcAGL-15 untuk penanda embriogenesis tanaman kakao melalui pendekatan bioinformatika Identification of TcAGL-15 homolog in the embryogenic culture from the zygotic embryo explant - Oktaviany Ferry TRIASTANTO; Muhammad JUSUF; Djoko SANTOSO (Menara Perkebunan, 2006)
Summary One of the major problems encountered in micropropagation of cacao through tissue culture is very low frequency of embryo formation. Embryogenesis is believed to have key regulatory gene determining the process. Understanding such gene may help to solve problems in the regeneration process. One of the genes reported to involve in the embryogenesis is AGAMOUS-like 15 (AGL-15). This gene has an important role in the regulation of early embryogenesis in several plants. This experiment aimed to identify AGL-15 homolog in cacao through bioinformatics approach. The first step of this experiment is to identify the AGL-15 homolog using hetero-logous primers from DNA genomic isolated from leaves of cacao plants. The sequence of the AGL-15 fragment was used in designing specific primers for longer AGL-15 fragment. These primers were then used to identify AGL-15 gene using total RNA isolated from cultured zygotic embryos. Differential pattern of AGL-15 gene expression was observed in zygotic embryos cultured for five weeks. AGL-15 heterologous primers designed from several plants could be used to identify cacao AGL-15 homolog. The putative cacao AGL-15 gene could be identified from zygotic embryos. The differential pattern of the AGL-15 gene expression is a strong indication that AGL-15 can be used as an embryogenesis marker in cacao plants.Ringkasan Salah satu kendala perbanyakan kakao melalui kultur jaringan adalah sulitnya embriogenesis, yang diduga melibatkan satu atau lebih gen kunci yang menentukan proses tersebut. Keberhasilan mengidentifikasi gen-gen kunci akan membantu menyelesaikan masalah dalam regenerasi embrio kakao. Salah satu gen yang diduga terlibat dalam proses ini adalah AGAMOUS-like 15 (AGL-15). Gen ini berperan pada regulasi selama masa awal perkembangan embrio beberapa tanaman. Penelitian ini bertujuan untuk mengidentifikasi homolog AGL-15 pada kakao melalui pen-dekatan bioinformatika dan RT-PCR. Pene-litian diawali dengan identifikasi homolog AGL-15 dari DNA genomik daun kakao meng-gunakan primer heterologus. Sekuen fragmen homolog AGL-15 yang diperoleh, kemudian digunakan untuk merancang primer spesifik AGL-15 yang berukuran lebih panjang. Primer ini selanjutnya digunakan untuk meng-identifikasi gen AGL-15 dari RNA total embrio zigotik. Pengamatan pola pita gen AGL-15 dilakukan pada kultur in vitro embrio zigotik yang berumur lima minggu. Primer hetero-logus gen AGL-15 yang berasal dari berbagai tanaman, mampu mengidentifikasi keberadaan homolog  gen  tersebut  pada  tanaman   kakao. Fragmen homolog AGL-15 putatif tanaman kakao teridentifikasi pada tingkat RNA embrio. Dengan adanya pola diferensial dari ekspresi gen AGL-15 hingga lima minggu pertama perkembangan embrio, ada indikasi kuat bahwa fragmen homolog AGL-15 dapat menjadi penanda embriogenesis pada tanaman kakao.